The Role of Bridging Therapy in Hepatocellular Carcinoma - Roberto Galuppo; Angie McCall; Roberto Gedaly (International Journal of Hepatology)
Hepatocellular carcinoma (HCC) is the most common primary malignancy of the liver accounting for 7% of all cancers worldwide. Most cases of HCC develop within an established background of chronic liver disease. For that reason, liver resection is only possible in selected patients. Liver transplantation has become the treatment of choice in patients with HCC, end-stage liver disease, and significant portal hypertension. Shortage of organ donors has resulted in overall increase of waiting list time with increased risk of dropout due to tumor progression. Neoadjuvant therapies have emerged as an alternative to control tumor growth in patients while waiting. The aim of this study is to review the literature on the role of bridging therapy and downstaging prior to liver transplantation in patients with HCC. We are also presenting our single-center experience of 96 patients undergoing transplantation for HCC with and without bridging therapy.